Language Analysis and Crosscultural Communication in the Movie “Ajari Aku Islam” by Haris Suhud and Yunita R Saragi - Khotimah, Asyiatul; Oktiana, Ulmi; Yulianti, Alvy Tri; Rahmani, Syafina Hikmah; Noviana, Dwi (UM Purwokerto Press, 2025)
Intercultural communication involves participants from different cultural backgrounds that influence the way they communicate. This study aims to analyze language and cross-cultural communication in the film “Ajari Aku Islam” by Haris Suhud and Yunita R Saragi, using critical theory based on the thoughts of Robert N. Entman. The analysis was conducted on different ethnic, religious and cultural backgrounds. This research applies a descriptive qualitative method with data collection using documentation techniques, as well as listening and note-taking techniques. This movie displays conflicts in a family with different religious and cultural backgrounds, which result in barriers in intercultural communication. The results showed that intercultural communication can run well if there is tolerance, an open mindset towards cultural differences, and the ability to adjust to the values, norms, and religions adopted by individuals or community groups.